Virtual Reality Head-Mounted Displays in Medical Education: A Systematic Review. Issue 1 (9th February 2023) - Tursø-Finnich, Thomas; Jensen, Rune Overgaard; Jensen, Lasse X.; Konge, Lars; Thinggaard, Ebbe
Summary Statement: Simulation-based training using virtual reality head-mounted displays (VR-HMD) is increasingly being used within the field of medical education. This article systematically reviews and appraises the quality of the literature on the use of VR-HMDs in medical education. A search in the databases PubMed/MEDLINE, Embase, ERIC, Scopus, Web of Science, Cochrane Library, and PsychINFO was carried out. Studies were screened according to predefined exclusion criteria, and quality was assessed using the Medical Education Research Study Quality Instrument. In total, 41 articles were included and thematically divided into 5 groups: anatomy, procedural skills, surgical procedures, communication skills, and clinical decision making. Participants highly appreciated using VR-HMD and rated it better than most other training methods. Virtual reality head-mounted display outperformed traditional methods of learning surgical procedures. Although VR-HMD showed promising results when learning anatomy, it was not considered better than other available study materials. No conclusive findings could be synthesized regarding the remaining 3 groups.